An enzyme-free electrochemical biosensor for sensitive and specific detection of microRNA-21 based on target recycling amplification and non-linear hybridization chain reaction - Jing Guo; Shou-feng Zhao; Shuang Chen; Wei-qing Song; Li-qun Li (Scientific Reports)
Abstract A novel electrochemical biosensor with high amplification efficiency was explored for serum microRNA-21 (miRNA-21) detection. This biosensor consisted of the target recycling amplification (TRA) and non-linear hybridization chain reaction (NHCR). When the target miRNA-21 was presented, hairpin probe 1 (HP1) could be opened and hybridized with target miRNA-21, the formation of DNA/RNA complexes could hybridize with hairpin probe 2 (HP2) and released target miRNA-21, resulting in the target recycling amplification. Then, the opened HP2 acted as a trigger chain and bonded to substrate-A to trigger NHCR. After the occurrence of NHCR, large amounts of high molecular weight double-stranded DNA were produced. Because the two basic chains, substrate-A and substrate-B, of the synthesized NHCR product were labeled with biotin, the NHCR product carried a large amount of biotin. When streptavidin-alkaline phosphatase (ST-AP) was added, it could combine with the biotin and catalyze the hydrolysis of α-naphthyl phosphate (α-NP) to α-naphthol. Since α-naphthol was electrically active, an ultrasensitive electrochemical readout was obtained. Based on the highly efficient signal amplification, the established biosensor showed an outstanding sensitivity for target miRNA-21 detection. The limit was as low as 0.8 fM, and the linear range was 1 fM to 10 nM. The research also verified that the biosensor had good stability and repeatability. Moreover, the detection results of spiked miRNA-21 in serum by this biosensor were in good agreement with those in the buffer solution. Due to its excellent ability, this new biosensor might have great potential for application in the detection of biomolecules and clinical disease diagnosis.